Historische Zeitschrift (De Gruyter Oldenbourg, 1859)
The Journal of History (HZ) is synonymous with excellent German language historiography. The article section encompasses aspects of all historical sub-disciplines - there is no regional or epochal restriction. An extensive section of book reviews, review articles on current trends and debates, and a list of works submitted for review keep the reader fully up to date on the latest state of German and international historical research.